2018
DOI: 10.1101/455071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil microbial communities with greater investment in resource acquisition have lower growth yield

Abstract: Resource acquisition and growth yield are fundamental traits of microorganisms that have consequences for ecosystem functioning. However, there is a lack of empirical observations linking these traits. Using a landscape-scale survey of temperate near-neutral pH soils, we show tradeoffs in key community-level parameters linked to these traits. Increased investment into extracellular enzymes was associated with reduced growth yield; this reduction was linked more to carbon than nitrogen acquisition enzymes sugge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 28 publications
5
23
0
Order By: Relevance
“…The SEM revealed that management drives microbial strategies through both soil and plant CWM trait modifications (Figure ). The observed decrease in mass‐specific enzymes activity with soil N content was in line with previous studies conducted along a 120,000‐year‐old soil development chronosequence in New Zealand (Allison et al, ), and across a large land use gradient in Britain (Malik, Puissant, et al, ). These results support the hypothesis that copiotrophs in nutrient‐rich soils invest less in the production of extracellular enzymes to acquire C and other nutrients from complex organic molecules (Fontaine et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The SEM revealed that management drives microbial strategies through both soil and plant CWM trait modifications (Figure ). The observed decrease in mass‐specific enzymes activity with soil N content was in line with previous studies conducted along a 120,000‐year‐old soil development chronosequence in New Zealand (Allison et al, ), and across a large land use gradient in Britain (Malik, Puissant, et al, ). These results support the hypothesis that copiotrophs in nutrient‐rich soils invest less in the production of extracellular enzymes to acquire C and other nutrients from complex organic molecules (Fontaine et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…EEC:EEP, EEC:EEN and EEN:EEP ratios were calculated to represent the balance of C versus P, C versus N and N versus P acquisition respectively (Sinsabaugh et al, ). Thirdly, mass‐specific enzymes activity was calculated as the total extracellular enzyme activities per unit of microbial biomass‐N and considered as a proxy of the average investment in extracellular enzyme production per unit of microbe within the community (Malik, Puissant, Goodall, Allison, & Griffiths, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictions regarding how soil C stocks will respond to climate change are, in turn, highly sensitive to how carbon use efficiency (CUE)-or the fraction of C taken up by a cell and incorporated into biomass rather than being respired--changes with temperature (Allison et al, 2010;Wieder et al, 2013;Allison, 2014;Li et al, 2014;Sistla et al, 2014;Tang and Riley, 2015). As such, quantifying microbial decomposer CUE and its responsiveness to environmental change has been subject to intensive study (Devêvre and Horwáth, 2000;Frey et al, 2013;Blagodatskaya et al, 2014;Lee and Schmidt, 2014;Spohn et al, 2016a, b;Öquist et al, 2017;Malik et al, 2018;Geyer et al, 2019;Malik et al, 2019;Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is because carbon which could otherwise be allocated to growing the cell or generating the energy required to maintain it must instead be spent producing amino acids and expending ATP to link them together (Kaleta et al, 2013;Kafri et al, 2016). As such, extracellular enzyme production is inferred to reduce the carbon use efficiency of soil microbial communities (Allison, 2014;Malik et al, 2019).…”
Section: Introductionmentioning
confidence: 99%